2020
DOI: 10.1007/s13202-020-00919-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent comprehensive review for extended finite element method (XFEM) based on hydraulic fracturing models for unconventional hydrocarbon reservoirs

Abstract: Hydraulic fracturing has been around for several decades since 1860s. It is one of the methods used to recover unconventional gas reservoirs. Hydraulic fracturing design is a challenging task due to the reservoir heterogeneity, complicated geological setting and in situ stress field. Hence, there are plenty of fracture modelling available to simulate the fracture initiation and propagation. The purpose of this paper is to provide a review on hydraulic fracturing modelling based on current hydraulic fracturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…He et al (2016) reviewed two possible methods to generate directional controlled hydraulic fractures in caving mining, pointed out that directional hydraulic fracturing and stress shadow effect could make the propagation trajectory of hydraulic fractures contrary to the direction predicted by theory and suggested that proppant should be introduced into cave mining to enhance the stress shadow effect. Maulianda et al (2020) summarized the numerical modeling of hydraulic fracturing and elaborated the basic theory of hydraulic fracturing simulation. Sheng et al (2015) reviewed the existing mathematical and computational models for modeling rock formation and hydrodynamic behavior, as well as some key studies and their basic results.…”
Section: Review Of Stress Shadow and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…He et al (2016) reviewed two possible methods to generate directional controlled hydraulic fractures in caving mining, pointed out that directional hydraulic fracturing and stress shadow effect could make the propagation trajectory of hydraulic fractures contrary to the direction predicted by theory and suggested that proppant should be introduced into cave mining to enhance the stress shadow effect. Maulianda et al (2020) summarized the numerical modeling of hydraulic fracturing and elaborated the basic theory of hydraulic fracturing simulation. Sheng et al (2015) reviewed the existing mathematical and computational models for modeling rock formation and hydrodynamic behavior, as well as some key studies and their basic results.…”
Section: Review Of Stress Shadow and Methodsmentioning
confidence: 99%
“…(3) Some scholars (from Universiti Teknologi Petronas, Malaysia; University of Calgary, Canada; Kansas University, USA) (Maulianda et al, 2020) summarized the numerical modeling of hydraulic fracturing and elaborated the basic theory of hydraulic fracturing simulation and the effort is made to cover the analytical and numerical modelling, while focusing on a typical numerical method for continuumdiscontinuum analysis: Extended Finite Element Modelling (XFEM).…”
Section: Review Of Stress Shadow and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of defining fractures individually and modelling the strength degradation, this means that the properties of the domain are generalised and modelled as a continuum. The region of interest can then be discretised based on the regions of high and low fracture density, allowing for the modelling of the fractured and virgin zones of the reservoir [18,39]. The use of an ECM representation makes it simpler to apply well established numerical approaches such as the finite element method (FEM) to solve governing equations that describe the physical processes and behaviour of the medium.…”
Section: Equivalent Continuum Methods (Ecm)mentioning
confidence: 99%
“…Although the continuum method has high computational efficiency, it cannot directly describe the fracture geometry, which is approximated by damage bands. To overcome the problem of fracture description, the extended finite element method (XFEM) adds the degree of freedom to simulate the fracture behavior (Maulianda, 2020). The fractures can then be expressed explicitly (Zheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%